2015
DOI: 10.1007/s12603-015-0543-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of atherogenic effects of low carbohydrate, high protein diet (LCHP) in apoE/LDLR−/− mice

Abstract: The pro-atherogenic effect of LCHP diet in apoE/LDLR-/- mice is associated with profound increase in LDL and VLDL cholesterol, VLDL triglicerides, liver SREBP-1 upregulation, and systemic inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…In this study atherosclerotic plaque analysis was focused on BCA lesions closely resembling those in human atherosclerosis. Our previous work clearly suggest that BCA’s are vessels of choice to reliably analyze efficacy and mechanisms of anti-atherosclerotic treatment in ApoE/LDLR −/− mice 16 .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In this study atherosclerotic plaque analysis was focused on BCA lesions closely resembling those in human atherosclerosis. Our previous work clearly suggest that BCA’s are vessels of choice to reliably analyze efficacy and mechanisms of anti-atherosclerotic treatment in ApoE/LDLR −/− mice 16 .…”
Section: Discussionmentioning
confidence: 92%
“…It was shown, that pro-atherogenic phenotype of LCHP fed ApoE/LDLR −/− mice was associated with increased plasma concentration of total cholesterol, LDL and VLDL cholesterol content, as well as increased triacylglycerols content in VLDL. These findings suggested that LCHP diet induced atherogenesis in ApoE/LDLR −/− mice was associated with cholesterol-driven mechanisms but other mechanisms could not be excluded 16 .…”
mentioning
confidence: 96%
“…Low-density lipoprotein (LDL) cholesterol, very low density lipoprotein cholesterol, HDL cholesterol, total cholesterol, and triglyceride plasma concentration were analyzed in plasma samples using the field flow fractionation method, with quantitative determination of cholesterol in lipoprotein fractions performed by enzymatic colorimetric assay (Kostogrys et al, 2015). High-performance liquid chromatography (HPLC) analysis was performed using an Agilent 1100 system and Agilent OpenLAB (C.01.05) software in combination with the appropriate Eclipse plugin (version 4; Agilent Technologies, Santa Clara, CA).…”
Section: Methodsmentioning
confidence: 99%
“…The inflammatory conditions of the atherosclerotic plaque are known to decrease NO levels by the means of oxidation by reactive oxygen species (Napoli et al 2006). On the other hand highprotein diet exerts a proaterogenic effect (Meeker and Kesten 1941;Kostogrys et al 2015). This effect can be attenuated by moderate physical activity, which is proved by lowered rate of atherosclerosis in running supplemented groups in comparison to non-running supplemented groups.…”
Section: Discussionmentioning
confidence: 99%